Gamma Radiation Shielding Properties of Slag and Fly Ash-based Geopolymers - M. W. Hasan; S. Sugiharto; S. Astutiningsih (PPIKSN-BATAN, 2021)
Industrial waste-based geopolymer cement is a greener alternative to Ordinary Portland Cement (OPC) for radiation shielding with comparable mechanical properties without the production of CO2 during synthesis. In this paper, the linear attenuation coefficient of slag and fly ash-based geopolymers, unmodified by aggregates, is measured and used to calculate the mass attenuation coefficients, half-value layer (HVL), and tenth-value layer (TVL) of the geopolymers. Narrow Beam Gamma Spectrometry with gamma energy of 0.662 MeV, 1.173 MeV, and 1.332 MeV was used to irradiate a series of slag and fly ash-based geopolymer paste of cylindrical shape with a diameter of 7.5 cm and height of 9.5 cm. Slag geopolymer has linear attenuation coefficient of 0.1642/cm, 0.1237/cm, 0.1150/cm, mass attenuation coefficient of 0.0782 cm2/g, 0.0589 cm2/g, 0.0548 cm2/g, the HVL of 4.222 cm, 5.609 cm, 6.056 cm, and TVL of 14.025 cm, 18.633 cm, 20.118 cm, respectively. Fly ash geopolymer has linear attenuation coefficient of 0.1387/cm, 0.1075/cm, and 0.0964/cm, mass attenuation coefficient of 0.0761 cm2/g, 0.0589 cm2/g, 0.0529 cm2/g, HVL of 4.998 cm, 6.453 cm, 7.202 cm, and TVL of 16.603 cm, 21.437 cm, 23.926 cm, respectively. Test samples made from slag-based geopolymers have a better shielding capability compared to fly ash-based geopolymers due to having higher attenuation coefficients as well as lower HVL and TVL, thus requiring less material to absorb radiation of the same energy level.